The Role of Social Media Marketing and Electronic Word of Mouth on the Purchase Intention of Frozen Meat Products - I Putu Gede Didik Widiarta; Dinar Anindyasari; Amalina Nur Wahyuningtyas (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2024)
In the modern digital era, technology and the internet have become essential components of marketing strategies. This study aims to investigate the influence of Social Media Marketing (SMM) and Electronic Word of Mouth (eWOM) on the purchase intention of frozen meat products in Samarinda, Indonesia. Understanding consumer response to online promotions is increasingly important, particularly in the food industry, given the expanding role of digital marketing. The research employs a quantitative approach, engaging 400 respondents across different age groups, genders, and education levels. Data was collected through structured questionnaires to gauge the impact of SMM and eWOM on purchase intention, as well as the moderating role of demographic factors. The analysis indicates that both SMM and eWOM significantly enhance purchase intention, with eWOM exhibiting a stronger influence. Younger consumers aged 20-35 and those with higher education levels are more susceptible to online reviews and social media promotions compared to older or less-educated consumers. Moreover, women display greater responsiveness to interactive marketing content than men. The study recommends that companies in the frozen meat industry focus their digital strategies on leveraging positive reviews and social media promotions to elevate consumer engagement and purchase intentions. These findings contribute to the body of knowledge on digital marketing and provide practical insights for marketers aiming to maximize the impact of digital campaigns in the contemporary era.